Coffee Berrie [sic] - Bryant, Herbert J. (Richardson and Selway Ltd., Trinidad, 2009)
A picture of a woman standing next to a basket full of coffee beans.
Colour: Coloured; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coffee--Trinidad and Tobago; Women--Trinidad and Tobago